ЎЗБЕК ВА ҚОРАҚАЛПОҚ ХАЛҚЛАРИДА ТЕЗ АЙТИШ ЖАНРИ ҚИЁСИЙ МУШТАРАКЛИГИ - Мадияров, И.Б. (SCIENCE and SOCIETY, 2018)
The article deals with summarizing of peculiarities of the genre of children's folkloretongue-twisters on the example of oral creative work of the Uzbek and Karakalpak people. The author in his analysis tries to evaluate the tendency of development of study of folklore of the Turkic people, national, inter literary andcommon typological, literary interpretation as well.
Keywords: folklore; tale; proverbs and sayings; puzzle; tongue-twisters